Linkages between the molecular composition of dissolved organic matter and soil microbial community in a boreal forest during freeze–thaw cycles - Yang, Yan; Cheng, Shulan; Fang, Huajun; Guo, Yifan; Li, Yuna; Zhou, Yi; Shi, Fangying; Vancampenhout, Karen (Frontiers in Microbiology, 2023)
Soil dissolved organic matter (DOM) plays a vital role in biogeochemical processes. Global warming leads to increased freeze-thaw cycles (FTCs) in boreal forest soils, which can change DOM production and consumption. However, the interactions between the chemical composition of DOM molecules and the microbial communities that drive C decomposition in the context of freeze-thaw are poorly understood. Here, a FTCs incubation experiment was conducted. Combined with pyrolysis gas chromatography-mass spectrometry (Py-GC/MS) and high-throughput sequencing techniques, the relationships between DOM chemodiversity and microbial community structure were assessed. Results indicated that both low-frequency (2FTCs) and high-frequency freeze-thaw cycles (6FTCs) significantly increased soil dissolved organic carbon (DOC) contents in the surface (0-10 cm) and subsurface (50-60 cm) soil layers. In the topsoil, FTCs significantly reduced the relative abundance of aromatic compounds, but increased the relative proportions of alkanes, phenols, fatty acid methyl esters (Me) and polysaccharides in the DOM. In the subsuface soil layer, only the relative abundance of Me in the 6FTCs treatment increased significantly. The response of bacterial communities to FTCs was more sensitive than that of fungi, among which only the relative abundance of Gammaproteobacteria increased by FTCs. Moreover, the relative abundance of these taxa was positively correlated with the increment of DOC. Co-occurrence networks confirmed DOM-bacterial interactions, implying that specific microorganisms degrade specific substrates. At class level, Gammaproteobacteria were significantly positively correlated with labile C (polysaccharides and alkanes), whereas other bacterial classes such as Actinobacteria, Alphaproteobacteria, and Thermoleophilia were significantly positively correlated with aromatic compounds in the topsoil. Collectively, FTCs tended to activate DOM and enhance its biodegradability of DOM, potentially hampering DOC accumulation and C sequestration. These findings highlight the potential of DOM molecular mechanisms to regulate the functional states of soil bacterial communities under increased FTCs.